Representing Suffering: Testimony at Rwanda's Gacaca Courts - Eramian, Laura (InTensions, 2008)
In this paper, I examine dominant understandings of subjects of suffering, the witness, and testimony in Rwanda‘s local level courts for genocide crimes, called gacaca. I begin from the observation that, in the Western legal and ontological traditions, the primary subject of both testimony and suffering is presumed to be the bounded, autonomous, possessive individual. I suggest that this understanding of the subject of testimony overlooks a central attribute of state-sponsored political violence, namely, that it is targeted at groups rather than individuals. The paper concludes with a number of questions and cautions about what it might mean to understand the collective, rather than the individual, as the primary subject of suffering and testimony.